The Qur’anic Exegetical Styles: A Research Study - Hafiz Muhammad Arshad Iqbal; Muhammad Tayyab Khan (Journal of Islamic and Religious Studies, 2021)
To comprehend the excegetical literature, acquantaning with excegetical syles alongwith their different dimensions is inevitable. Exegesis by tradition(Tafsīr bil Ma’thūr) is very first style adopted in the interpretation of excegisis. Here is the the importance and significanse of the this study lies. Now the question is that how many sorts of this style of interpretation are there and what are the contents of its sorts. There are six kinds of this syles of Qur’ānic interpretation. The exegiest and the scholars of Qur’ān and Tafsir usually don’t take on these kinds as whole. That is why the study has more significance and bears importance. The study aims to know the kinds  of exegesis by tradition(Tafsīr bil Ma’thūr) with changing in it with the passage of time. There are many subdivisions and details concerning these kinds of Tafsīr bil ma’thūr. An analytical method of the research is followed during this research. It is pertinent to mention that the study is equipped with the examples of Tafsīr bil ma’thūr; for any claim and statement without existentioal evidence cannot be comprehencible.  In addition to this, changes in the dealing of this style of Qur’ānic interpretation with time can also be observed. This study particularly revolves around the Tafsīr bil ma’thūr.